A preparation method and application of aluminum alloy extruded profile

By forming ultrafine subcrystals and nano-scale reinforced phases in aluminum alloys and using specific components and processes, the problem that existing aluminum alloy materials are difficult to meet the requirements of high strength, fatigue resistance and corrosion resistance at the same time is solved, and the material performance is significantly improved, meeting the lightweight material needs of automobiles.

CN116334455BActive Publication Date: 2025-04-01WEIQIAO LIGHTWEIGHT RESEARCH CENTER AT SOOCHOW
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310223108.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-04-01
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

The materials of the existing 6XXX aluminum alloy system are difficult to meet the requirements of high strength, fatigue resistance, corrosion resistance and light weight at the same time, and the fatigue performance is poor, making it difficult to meet the development needs of the automobile industry.

Method used

By forming a large number of ultrafine subcrystals and nano-scale reinforced phases in the aluminum alloy, specific ingredients, heat treatment systems and extrusion processes are adopted, including melting casting, homogenization treatment, extrusion treatment and aging treatment, to improve the strength, fatigue resistance and corrosion resistance of the aluminum alloy.

Benefits of technology

It has achieved the improvement of high strength, fatigue resistance and corrosion resistance of aluminum alloys. The yield strength can exceed 400MPa, the elongation is greater than 10%, and the fatigue strength is greater than 150MPa, which solves the problem of low performance of traditional 6XXX aluminum alloys and meets the automotive lightweight material needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116334455B_ABST
    Figure CN116334455B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an aluminum alloy extruded profile, belonging to the technical field of alloy processing. The preparation method comprises preparing the aluminum alloy according to a certain composition ratio, melting and casting the prepared materials and homogenizing the prepared materials, so that a uniformly distributed nano-scale AlFe(MnCr)Si dispersed phase is formed inside the aluminum alloy grains, and the aluminum alloy ingot after homogenization is extruded and aged according to certain extrusion processing conditions. The invention forms a large number of ultrafine subgrains and nano-scale strengthening phases in the deformed structure through composition design, heat treatment system and extrusion process, and improves the strength, fatigue resistance and corrosion resistance of the aluminum alloy through the synergistic effect of ultrafine subgrains and nano-scale strengthening phases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy processing, and in particular to the application of a method for preparing an aluminum alloy extruded profile for lightweight automobiles. Background Art

[0002] Aluminum alloy profile extrusion technology has always been a key technology in the field of aluminum alloy profile deep processing. For high-strength and high-service performance aluminum alloy profiles for lightweight automobiles, how to obtain high-strength, fatigue-resistant, corrosion-resistant, and lightweight aluminum alloy profiles is the ultimate goal pursued by practitioners. However, at present, the existing 6XXX aluminum alloy system materials are difficult to meet the above product goals and characteristics at the same time. Only 6061 and 6082 aluminum alloy profiles or forgings can be produced domestically, and the product performance stability is low, especially the fatigue performance is poor, and the technical level is difficult to meet the development of the automotive industry. Summary of the invention

[0003] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing an aluminum alloy extruded profile and its application, so as to form a large number of ultrafine subgrains and nano-scale strengthening phases in the aluminum alloy structure and improve the strength, fatigue resistance and corrosion resistance of the aluminum alloy.

[0004] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing an aluminum alloy extruded profile, comprising the following steps:

[0005] S1. Prepare the ingredients according to the following mass percentages: Si: 0.8-1.4, Mg: 0.7-1.2, Cu: 0.3-0.8, Mn: 0.4-0.8, Cr: 0.2-0.4, Ti≤0.03, Fe≤0.15, Zn≤0.2, single impurity≤0.02, total impurity≤0.1, and the balance is Al;

[0006] S2, performing melting, casting and homogenization treatment on the ingredients, so that a uniformly distributed nano-scale AlFe(MnCr)Si dispersed phase is formed inside the aluminum alloy grains;

[0007] S3, performing extrusion processing according to certain extrusion processing conditions, so that the aluminum alloy grains in the extruded profile form ultrafine sub-grains;

[0008] S4. Perform aging treatment on the extruded profile.

[0009] The alloy composition control of the ratio can make Mn and Cr be dissolved in the aluminum matrix to the greatest extent during the semi-continuous casting process, so that they precipitate to form a nano-scale Al(FeMnCr)Si dispersed phase during the subsequent homogenization heat treatment process.

[0010] Preferably, the homogenization process in S2 includes:

[0011] The first stage is homogenization treatment, which is carried out at a temperature of 250-400°C for 6-10 hours;

[0012] The second stage is homogenization treatment, which is carried out at a temperature of 530-565°C for 10-15h;

[0013] The cooling is performed at a cooling rate of 100-800°C / h.

[0014] Preferably, the heating rate during the homogenization treatment is ≤3°C / min.

[0015] Preferably, in the S2, the size of the nano-scale AlFe(MnCr)Si dispersed phase is 20-350 nm.

[0016] Preferably, in S3, during the profile extrusion process, the heating temperature of the hot end of the cast rod does not exceed 510°C, the heating gradient is 20-80°C / m, the extrusion outlet temperature is 520-570°C, and the extrusion ratio is 22-60.

[0017] Preferably, S3 includes quenching the profile at an online quenching rate of not less than 700° C. / min.

[0018] Preferably, the aging treatment in S4 includes performing T5 or T6 aging treatment on the profile.

[0019] Preferably, the size of the ultrafine sub-grains in the extruded profile is 2-10 um, and the proportion of small-angle grain boundaries with an angle less than 15° is greater than 60%.

[0020] Preferably, in S3, the average size of subgrains in the extruded profile is below 10 μm, the proportion of subgrains is ≥78% (greater than or equal to 78%), the proportion of substructure organization is ≥60% (greater than or equal to 60%), and the proportion of recrystallized organization is <30% (less than 32%).

[0021] The present invention also proposes an application of an aluminum alloy extruded profile, which is applied to fuel vehicles or electric vehicles, including front and rear anti-collision beams, front and rear longitudinal beams, door sill beams, seat cross beams, dashboard frames, and battery pack frames.

[0022] The beneficial effects of the present invention are as follows: the present invention forms a large number of ultrafine subgrains and nano-scale strengthening phases in the deformed structure of the aluminum alloy through component design, heat treatment system and extrusion process, and the high strength, fatigue resistance and corrosion resistance of the aluminum alloy are simultaneously improved through the synergistic effect of ultrafine subgrains and nano-scale strengthening phases. For 6XXX aluminum alloys with high strength, fatigue resistance, excellent corrosion resistance and extrudability, the yield strength can be up to more than 400MPa, the elongation is greater than 10%, the fatigue strength is greater than 150MPa, and the intergranular corrosion performance is better than that of 6082 alloy, which solves the problem that the traditional 6XXX aluminum alloy has low performance and limits its large-scale application, and meets the urgent demand for lightweight automobiles for lightweight, high-strength and good service performance raw materials.

[0023] The high-toughness, fatigue-resistant and corrosion-resistant 6XXX aluminum alloy material of the present invention is applied to the front and rear anti-collision beams, front and rear longitudinal beams, door sill beams, seat cross beams, instrument panel frame (Cross CarBeam, CCB for short), battery pack frame and other parts systems of automobiles, which can reduce the weight of the entire vehicle body by 15% or more. For fuel vehicles, the average fuel consumption is saved by more than 8%, and the service life is expected to increase by more than 3 years. During the entire service life, exhaust emissions can be reduced by more than 30kg; for electric vehicles, the expected cruising range is increased by more than 250km. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a schematic diagram of the dispersed phase distribution after the sample is homogenized in Example 1 of the present invention;

[0025] Figure 2 This is the OM structure diagram of the WHS profile and the 6082 profile subjected to the intergranular corrosion experiment in Example 1 of the present invention;

[0026] Figure 3 This is a comparison chart of the corrosion performance of the WHS profile and the 6082 profile in the intergranular corrosion test of the embodiment 1 of the present invention;

[0027] Figure 4 This is a subgrain structure diagram of the WHS extruded profile alloy in the T5 state in Example 1 of the present invention;

[0028] Figure 5 This is a graph of subgrain orientation distribution and grain size distribution in the T5 state of the WHS extruded profile alloy in Example 1 of the present invention;

[0029] Figure 6 This is a deformation microstructure distribution diagram and a proportion diagram of the WHS extruded profile alloy in the T5 state in the first embodiment of the present invention;

[0030] Figure 7 is a schematic diagram of the dispersed phase distribution after the sample of Example 2 of the present invention is homogenized;

[0031] Figure 8 This is the OM structure diagram of the intergranular corrosion experiment of the WHS profile and the 6082 profile in Example 2 of the present invention;

[0032] Fig. 9 This is a subgrain structure diagram of the WHS extruded profile alloy in the T5 state according to the second embodiment of the present invention;

[0033] Fig.10 This is a graph showing the subgrain orientation distribution and grain size distribution of the WHS extruded profile alloy in the T5 state according to the second embodiment of the present invention;

[0034] Fig.11 This is a deformation microstructure distribution diagram and a proportion diagram of the WHS extruded profile alloy in the T5 state in the second embodiment of the present invention;

[0035] Fig.12 is a schematic diagram of the dispersed phase distribution after the homogenization treatment of the sample in Example 3 of the present invention;

[0036] Fig.13 is a mechanical properties diagram of the sample of Example 3 of the present invention;

[0037] Fig.14 This is the OM structure diagram of the intergranular corrosion experiment of the WHS profile and the 6082 profile in Example 3 of the present invention;

[0038] Fig.15 This is a subgrain structure diagram of the WHS extruded profile alloy in the T5 state in Example 3 of the present invention;

[0039] Fig.16 This is a graph showing the subgrain orientation distribution and grain size distribution of the WHS extruded profile alloy in the T5 state in Example 3 of the present invention;

[0040] Fig.17 It is a deformation microstructure distribution diagram and proportion diagram of the WHS extruded profile alloy in the T5 state in Example 3 of the present invention. DETAILED DESCRIPTION

[0041] The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. The structural, method, or functional changes made by ordinary technicians in the field according to these embodiments are all included in the protection scope of the present invention.

[0042] Embodiment 1

[0043] The method for preparing the aluminum alloy extruded profile proposed in this embodiment comprises the following preparation steps:

[0044] Step 1: Ingredients are prepared according to the following mass percentages: Si: 1.4, Mg: 1.2, Cu: 0.8, Mn: 0.8, Cr: 0.4, Ti: 0.01, Fe: 0.15, Zn: 0.02, individual impurities ≤ 0.02, total impurities ≤ 0.1, and the balance is Al. The above ingredients are melted and cast to produce aluminum alloy ingots.

[0045] Step 2: homogenization treatment, the first stage homogenization treatment is carried out at a temperature of 350°C for 10 hours, and then the second stage homogenization treatment is carried out at a temperature of 565°C for 15 hours, and then strong wind cooling is carried out to obtain an aluminum alloy ingot with a uniformly distributed nano-scale AlFe(MnCr)Si dispersed phase, such as Figure 1 The diagram shows the distribution of the dispersed phase. Figure 1 It can be seen that the dispersed phase is fine and uniform.

[0046] Step 3: The aluminum alloy ingot is extruded according to the extrusion process with the hot end heating temperature of the cast rod being 510°C, the heating gradient being controlled at 80°C / m, the extrusion speed being controlled at 5mm / s, the extrusion outlet temperature being 550-570°C, and the extrusion ratio being 33. The homogenized ingot is extruded, and the extruded profile is quenched online at an online quenching rate of 820°C / min.

[0047] Step 4: Aging treatment: After the online quenching, the profile is stretched and straightened, and then the profile is aged according to the aging process system that the parking time before aging does not exceed 24 hours, the profile is kept at 180℃ in the aging furnace for 12 hours, and the profile is aged in the air-cooled state after being taken out of the furnace.

[0048] After aging, the chemical composition, mechanical properties, fatigue properties, corrosion resistance and microstructure were tested. The mechanical properties and fatigue properties are shown in Tables 1 and 2 below.

[0049] Table 1 Mechanical properties of the samples of Example 1

[0050]

[0051] Table 2 Fatigue properties of samples of Example 1

[0052]

[0053] Figure 2 and Figure 3 The OM structure diagram and corrosion performance comparison diagram of the WHS profile and 6082 profile in the intergranular corrosion test in this embodiment are shown. Figure 2 and Figure 3It can be seen that the average corrosion depth of the WHS alloy profile in the ED direction is 106μm, while the corrosion depth of the 6082 alloy profile in the ED direction is 347μm. In the ED direction, the corrosion resistance of the WHS alloy is 69% higher than that of the 6082 alloy profile; the average corrosion depth of the WHS alloy profile in the TD direction is 109μm, while the corrosion depth of the 6082 alloy profile in the TD direction is 369μm. In the TD direction, the corrosion resistance of the WHS alloy is 70% higher than that of the 6061. Therefore, in terms of overall performance, the corrosion resistance of the WHS alloy is 69.5% higher than that of the 6082 alloy.

[0054] The good corrosion resistance of WHS alloy profiles is due to its thin coarse-grained layer and its low recrystallization ratio. The fibrous deformation structure and the large number of ultrafine subgrains inside it effectively hinder the rate and path of corrosion extension along the grain boundaries. Therefore, WHS alloy has excellent corrosion resistance compared to traditional 6XXX alloys.

[0055] Figure 4 is the subgrain structure diagram of the WHS extruded profile alloy in the T5 state in this embodiment, Figure 5 is the subgrain orientation distribution and grain size distribution of the WHS extruded profile alloy in the T5 state in this embodiment, Figure 4 and Figure 5 The results of substructure orientation difference show that the proportion of small-angle grain boundaries less than 2° is as high as 47%, the proportion of small-angle grain boundaries between 3° and 10° is 17.4%, and the proportion of small-angle grain boundaries between 10° and 15° is 2.6%. In summary, the proportion of a large number of small-angle subgrains (ultrafine subgrains of <15°) in the deformed structure of the profile is 67%, reaching the target value, and the proportion of grains with low orientation difference less than 10μm reaches 82.3%, reaching the target value. A large number of ultrafine subgrains ensure the strength, toughness, fatigue resistance and corrosion resistance of the profile.

[0056] Figure 6 is the deformation structure distribution diagram and proportion of the WHS extruded profile alloy in the T5 state in this embodiment, Figure 6 It can be seen that the recrystallization fraction of the WHS alloy is 21.3%, the substructure fraction is 65%, and the deformed structure fraction is 13.6%; the subgrained structure is mainly composed of Substructured (substructure, 2°<grain boundary orientation difference<15°) and Deformed (deformed structure, grain boundary orientation difference<2°), so the subgrained structure accounts for the sum of the two. It can be seen that the subgrained structure of the WHS alloy can reach 78.7%.

[0057] Embodiment 2

[0058] The method for preparing the aluminum alloy extruded profile proposed in this embodiment comprises the following preparation steps:

[0059] Step 1: Ingredients are prepared according to the following mass percentages: Si: 1.0, Mg: 0.9, Cu: 0.5, Mn: 0.6, Cr: 0.3, Ti: 0.01, Fe: 0.15, Zn: 0.02, individual impurities ≤ 0.02, total impurities ≤ 0.1, and the balance is Al. The above ingredients are melted and cast to produce aluminum alloy ingots.

[0060] Step 2: homogenization treatment, the first stage homogenization treatment is carried out at a temperature of 300°C for 10 hours, and then the second stage homogenization treatment is carried out at a temperature of 560°C for 15 hours, and then strong wind cooling is carried out to obtain an aluminum alloy ingot with a uniformly distributed nano-scale AlFe(MnCr)Si dispersed phase, such as Figure 7 The figure shows a schematic diagram showing that the dispersed phase is small and evenly distributed.

[0061] Step 3: The aluminum alloy ingot is extruded, and the hot end heating temperature of the cast rod is 500℃, the heating gradient is controlled at 50℃ / m, the extrusion speed is controlled at 4mm / s; the extrusion outlet temperature is controlled at 540-570℃, and the extrusion ratio is 59. The homogenized ingot is extruded by an extrusion process, and then the extruded profile is quenched online at an online quenching rate of 750℃ / min.

[0062] Step 4: Aging treatment. After the online quenching, the profile is stretched and straightened, and then the profile is aged according to the aging process system that the parking time before aging does not exceed 24 hours. The profile is kept at 175°C in the aging furnace for 12 hours, and then air-cooled after being taken out of the furnace.

[0063] After aging, the chemical composition, mechanical properties, fatigue properties, corrosion resistance and microstructure were tested. Tables 3 and 4 show the mechanical properties and fatigue properties of the samples.

[0064] Table 3 Mechanical properties of samples of Example 2

[0065]

[0066]

[0067] Table 4 Fatigue properties of samples of Example 2

[0068]

[0069] Figure 8 The OM structure diagram of the WHS profile and 6082 profile used in this embodiment for intergranular corrosion experiment is shown. Figure 8It can be seen that the average corrosion depth of the WHS alloy profile in the ED direction is 171μm, while the corrosion depth of the 6082 alloy profile in the ED direction is 508.33μm. In the ED direction, the corrosion resistance of the WHS alloy is 66% higher than that of the 6082 alloy; the average corrosion depth of the WHS alloy profile in the TD direction is 154μm, while the corrosion depth of the 6082 alloy profile in the TD direction is 486.81μm. In the TD direction, the corrosion resistance of the WHS alloy is 68% higher than that of the 6082 alloy; therefore, in terms of overall performance, the corrosion resistance of the WHS alloy is 67% higher than that of the 6082 alloy.

[0070] The good corrosion resistance of WHS alloy profiles is due to its thin coarse-grained layer and its low recrystallization ratio. The fibrous deformation structure and the large number of ultrafine subgrains inside it effectively hinder the rate and path of corrosion extension along the grain boundaries. Therefore, WHS alloy has excellent corrosion resistance compared to traditional 6XXX alloys.

[0071] Fig. 9 is the subgrain structure diagram of the WHS extruded profile alloy in the T5 state of this embodiment, Fig.10 is the subgrain orientation distribution and grain size distribution of the WHS extruded profile alloy in the T5 state of this embodiment, Fig. 9 and Fig.10 The results of substructure orientation difference show that the small angle grain boundary less than 2° accounts for 41%, the small angle grain boundary of 3° to 10° accounts for 28%, and the small angle grain boundary of 10° to 15° accounts for 8%. In summary, the deformation structure of the profile has a large number of small angle subgrains (ultrafine subgrains of <15°) accounting for 77%, reaching the target value, and the grains with low orientation difference less than 10μm account for 84.4%, reaching the target value. A large number of ultrafine subgrains ensure the toughness, fatigue resistance and corrosion resistance of the profile.

[0072] Fig.11 is the deformation structure distribution diagram and proportion of the WHS extruded profile alloy in the T5 state of this embodiment, Fig.11 It can be seen that the recrystallization fraction of the WHS alloy is 24.5%, the substructure fraction is 64.8%, and the deformed structure fraction is 10.8%; the subgrained structure is mainly composed of Substructured (substructure, 2°<grain boundary orientation difference<15°) and Deformed (deformed structure, grain boundary orientation difference<2°), so the subgrained structure accounts for the sum of the two. It can be seen that the subgrained structure of the WHS alloy can reach 75.6%.

[0073] Embodiment 3

[0074] The method for preparing the aluminum alloy extruded profile proposed in this embodiment comprises the following preparation steps:

[0075] Step 1: Ingredients are prepared according to the following mass percentages: Si: 0.8, Mg: 0.7, Cu: 0.4, Mn: 0.4, Cr: 0.2, Ti: 0.01, Fe: 0.15, Zn: 0.02, individual impurities ≤ 0.02, total impurities ≤ 0.1, and the balance is Al. The above ingredients are melted and cast to produce aluminum alloy ingots.

[0076] Step 2: homogenization treatment, the first stage homogenization treatment is carried out at a temperature of 250°C for 8 hours, and then the second stage homogenization treatment is carried out at a temperature of 560°C for 12 hours, and then strong wind cooling is carried out to obtain an aluminum alloy ingot with a uniformly distributed nano-scale AlFe(MnCr)Si dispersed phase, such as Fig.12 The figure shows a schematic diagram showing that the dispersed phase is small and evenly distributed.

[0077] Step 3: The aluminum alloy ingot is extruded, and the hot end heating temperature of the cast rod is 490°C, the heating gradient is controlled at 30°C / m, the extrusion speed is controlled at 6mm / s; the extrusion outlet temperature is controlled at 530-550°C, and the extrusion ratio is 41. The homogenized ingot is extruded by an extrusion process, and then the extruded profile is quenched online at an online quenching rate of 980°C / min.

[0078] Step 4: Aging treatment. After the online quenching, the profile is stretched and straightened, and then the profile is aged according to the aging process system that the parking time before aging does not exceed 24 hours. The profile is kept at 175°C in the aging furnace for 10 hours, and then air-cooled after being taken out of the furnace.

[0079] After aging, the chemical composition, mechanical properties, fatigue properties, corrosion resistance and microstructure are tested. Mechanical properties such as Fig.13 As shown by Fig.13 It can be seen that the lower limit composition of WHS alloy is defined as WHS-2 alloy. After tensile testing, it can be seen that its yield strength can reach 391Mpa.

[0080] The fatigue properties are shown in Table 5 below.

[0081] Table 5 Fatigue properties of three WHS alloy profiles in Example

[0082] Sample No. Dimensions / mm Stress ratio Test frequency / HZ Maximum stress / MPa Cycle times WHS-2 9.98*4.95 -1 40 140 >1.0*107

[0083] Fig.14 The OM microstructure diagram of intergranular corrosion of WHS alloy and 6082 alloy used in this embodiment is shown. Fig.14It can be seen that the average corrosion depth of the WHS alloy profile in the ED direction is 160.42μm, while the corrosion depth of the 6082 alloy profile in the ED direction is 508.33μm. In the ED direction, the corrosion resistance of the WHS alloy is 68% higher than that of the 6082 alloy; the average corrosion depth of the WHS alloy profile in the TD direction is 179.7μm, while the corrosion depth of the 6082 alloy profile in the TD direction is 486.81μm. In the TD direction, the corrosion resistance of the WHS alloy is 63% higher than that of the 6082 alloy; therefore, in terms of overall performance, the corrosion resistance of the WHS alloy is 65.5% higher than that of the 6082 alloy.

[0084] The good corrosion resistance of WHS alloy profiles is due to its thin coarse-grained layer and its low recrystallization ratio. The fibrous deformation structure and the large number of ultrafine subgrains inside it effectively hinder the rate and path of corrosion extension along the grain boundaries. Therefore, WHS alloy has excellent corrosion resistance compared to traditional 6XXX alloys.

[0085] Fig.15 This is the subgrain structure diagram of the WHS extruded profile alloy in the T5 state of this embodiment, Fig.16 The subgrain orientation distribution and grain size distribution of WHS extruded profile alloy in T5 state are measured. Fig.15 and Fig.16 The results show that the small-angle grain boundaries less than 2° account for 37%, the small-angle grain boundaries between 3° and 10° account for 30%, and the small-angle grain boundaries between 10° and 15° account for 10%. In summary, there are a large number of small-angle subgrains (ultrafine subgrains of <15°) in the deformed structure of the profile, accounting for 77%, reaching the target value, and the grains with low orientation difference less than 10μm account for 87%, reaching the target value. A large number of ultrafine subgrains ensure the toughness, fatigue resistance and corrosion resistance of the profile.

[0086] Fig.17 is the deformation structure distribution diagram and proportion of the WHS extruded profile alloy in the T5 state in this embodiment, Fig.17 It can be seen that the recrystallization fraction of the WHS alloy is 31.6%, the substructure fraction is 63.1%, and the deformed structure fraction is 5.3%; the subgrained structure is mainly composed of Substructured (substructure, 2°<grain boundary orientation difference<15°) and Deformed (deformed structure, grain boundary orientation difference<2°), so the subgrained structure accounts for the sum of the two. It can be seen that the subgrained structure of the WHS alloy can reach 68.4%.

[0087] The preparation conditions in the aluminum alloy extruded profile preparation method in some comparative embodiments of the present invention and the chemical composition, mechanical properties, fatigue properties, corrosion resistance, microstructure and other properties of the prepared profiles are shown in Table 6 below.

[0088] Table 6 Preparation conditions and performance of samples of comparative examples 4 to 12

[0089]

[0090]

[0091] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for preparing an aluminum alloy extruded profile, characterized in that: The following steps are involved: S1. Prepare the following ingredients in percentage by mass: Si: 0.8-1.4, Mg: 0.7-1.2, Cu: 0.3-0.8, Mn: 0.4-0.8, Cr: 0.2-0.4, Ti≤0.03, Fe≤0.15, Zn≤0.2, single impurity≤0.02, total impurity≤0.1, and the balance is Al; S2, melting and homogenizing the ingredients to form a uniformly distributed nano-scale AlFe(MnCr)Si dispersed phase inside the aluminum alloy grains, wherein the homogenization treatment includes homogenization treatment at a temperature of 250-400° C. for 6-10 hours and at a temperature of 530-565° C. for 10-15 hours; S3, performing extrusion processing according to certain extrusion processing conditions, so that the aluminum alloy grains in the extruded profile form ultrafine subgrains, and the size of the ultrafine subgrains is 2-10; S4. Perform aging treatment on the extruded profile.

2. The method for preparing an aluminum alloy extruded profile according to claim 1, characterized in that: The step S2 also includes cooling at a cooling rate of 100-800° C. / h after the homogenization treatment.

3. The method for preparing an aluminum alloy extruded profile according to claim 2, characterized in that: The heating rate during the homogenization treatment is ≤3°C / min.

4. The method for preparing an aluminum alloy extruded profile according to claim 1, characterized in that: In the S2, the size of the nano-scale AlFe(MnCr)Si dispersed phase is 20-350nm.

5. The method for preparing an aluminum alloy extruded profile according to claim 1, characterized in that: In S3, during the profile extrusion process, the heating temperature of the hot end of the cast rod does not exceed 510°C, the heating gradient is 20-80°C / m, the extrusion outlet temperature is 520-570°C, and the extrusion ratio is 22-60.

6. The method for preparing an aluminum alloy extruded profile according to claim 1, characterized in that: The S3 includes quenching the profile at an online quenching rate of not less than 700° C. / min.

7. The method for preparing an aluminum alloy extruded profile according to claim 1, characterized in that: The aging treatment in S4 includes performing T5 or T6 aging treatment on the profile.

8. The method for preparing an aluminum alloy extruded profile according to claim 1, characterized in that: In S3, the proportion of small-angle grain boundaries with ultrafine subgrains having an angle of less than 15° in the extruded profile is greater than 60%.

9. The method for preparing an aluminum alloy extruded profile according to claim 1, characterized in that: In S3, the average size of subgrains in the extruded profile is less than 10 μm, the proportion of subgrains is ≥78%, the proportion of substructure is ≥60%, and the proportion of recrystallized structure is <32%.

10. Use of an aluminum alloy extruded profile prepared by the method for preparing an aluminum alloy extruded profile according to any one of claims 1 to 9, characterized in that: The aluminum alloy extruded profile is applied to fuel vehicles or electric vehicles.

Citation Information

Patent Citations

  • High-strength high-toughness Al-Mg-Si-Cu wrought aluminum alloy and preparation method thereof

    CN102337434A

  • High-strength Al-Mg-Si-Mn deforming aluminum alloy and preparing method thereof

    CN109666824A

  • High-performance low-carbon secondary aluminum extruded profile and preparation method thereof

    CN115261649A